Thomas King : Works and Impact. - Gruber, Eva (European studies in North American literature and culture., 2012)
Thomas King is one of North America's foremost Native writers, best known for his novels and short stories, but also a poet, a literary and cultural critic, and a noted filmmaker, photographer, and radio writer and performer. His work has been validated by literary awards and by its widespread inclusion in college and university curricula. Critical responses to King's work have been abundant, yet most of this criticism consists of journal articles, and to date only one book-length study of his work exists. This volume fills this gap by providing an up-to-date, comprehensive overview of all maj.